Studi Analisis Kinerja Jalan Trans Sumatra Terhadap Pengaruh Aktivitas Kendaraan di Wisata Pantai Pasir Putih - Perangin Angin, Imanuel Kemenangenta (Jurnal Informasi, Sains dan Teknologi, 2025)
The area of Pasir Putih beach is a recreational place for the people in Lampung province. Visitors to Pasir Putih Beach who bring vehicles can cause conflicts of delay that may lead to long queues on the Trans Sumatra Highway. This research aims to determine the performance of the Trans Sumatra road concerning the influence of the Pasir Putih Beach tour ist attraction using an unsignalized deviation approach caused by the impact of vehicle activities entering and leaving teh Pasir Putih Beach tourist spot.This is analyzed through road capacity regarding the degree of sautration (DS) and delay time (D) values of vehicles causes by the activities of vehicles entering and exiting at the Pasir Putih Beach tourist attraction. The results of the survey conducted in the field and the analysis of calculations obtained a saturation degree value on regular days of 0,59 and delay time value of 11,34 seconds/smp.